2019
DOI: 10.1002/pola.29386
|View full text |Cite
|
Sign up to set email alerts
|

Visible light‐induced metal‐free atom transfer radical polymerization: An efficient approach to polyacrylonitrile

Abstract: A visible light‐induced metal‐free atom transfer radical polymerization strategy for the efficient synthesis of polyacrylonitrile (PAN) with predictable molecular weights and low dispersities has been developed. High conversions can be obtained by using commercially available organic dyes as the photocatalysts under mild conditions in a living/controlled manner. Moreover, PAN can be obtained with moderate conversion under the irradiation of sunlight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…First, the catalyst of low-cost transition metal is sensitive to air, leading to the anaerobic polymerization. Second, the residual catalyst has certain toxicity to the protein [ 25 , 29 ]. Therefore, improved ATRP needs to be explored for better use in the preparation of protein imprinted polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the catalyst of low-cost transition metal is sensitive to air, leading to the anaerobic polymerization. Second, the residual catalyst has certain toxicity to the protein [ 25 , 29 ]. Therefore, improved ATRP needs to be explored for better use in the preparation of protein imprinted polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, these photocatalyst has a high excited oxidation potential and can initiate the polymerization by dechlorinating the halide (initiator of ATRP) to provide radical species. MVL ATRP has a simple operation, fast polymerization rate, high conversion rate, mild polymerization condition, more importantly, it can obtain both well-defined polymers and no metal pollution [ 29 , 32 , 33 ]. Fluorescein is a photocatalyst commonly used in MVL ATRP, which has visible light absorption, good chemical stability, long excited state lifetime and good redox potential [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…They present the advantages of being commercially available, simple operation, low cost, and the possibility of mediating polymerizations in aqueous media. [ 71,72 ] However, these dyes usually achieve lower initiation efficiencies because of the presence of co‐initiators causing unavoidable side reactions. [ 72,73 ] In all xanthene‐catalyzed photopolymerizations, it has been suggested that the irradiated dye is excited to the triplet state and abstracts a hydrogen from the electron donor species originating two radicals.…”
Section: Components Of O‐atrpmentioning
confidence: 99%
“…Other monomers like St and vinyl‐pyridine (4VP) were also tested and the results were considered satisfactory. [ 72 ]…”
Section: Components Of O‐atrpmentioning
confidence: 99%
“…Moreover, the introduction of light as an external stimulus in polymerization not only optimizes the reaction conditions, but also achieves the design, synthesis and precise control of complex systems. [15][16][17][18][19] Photo-induced living radical polymerization have been reported in numerous studies, [20][21][22] among which the photo-induced electron transfer-reversible addition-fragmentation chain transfer (PET-RAFT) polymerization is recognized to be a versatile technique for the synthesis of tailored polymers and fabrication of advanced materials. This so-called PET-RAFT is mediated by photocatalysts that can transfer electrons from excited states to chain transfer agents (CTAs) to generate radicals with the irradiation of light and initiate polymerization.…”
Section: Introductionmentioning
confidence: 99%